Politisch relevanter Totenkult - Januschke, Eugen (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
In Germany a new cult of the dead soldier is emerging. Whoever thinks this cult is only an antiquated custom of military rituals, which should be done away with, or whoever declares this cult to be an object of political discussion of only secondary rank, is missing one of the important political and sociological dimensions of the changing reproduction of the military in the time of the Afghanistan war. The article shows which necessary contribution this cult of the dead makes to Germany’s ability to wage war. Two important functions of this cult can be made out: to maintain the soldiers’ motivation, and the population’s acceptance of dead soldiers due to the war. The article focuses on the second function.